Re-entry problems: the post-prison challenges and experiences of former political prisoners in South Africa and Northern Ireland - Rolston, Bill; Artz, Lillian (The international journal of human rights, 2014)
Re-entry into society after imprisonment is problematic. However, politically motivated prisoners can potentially draw on their collective solidarity and social legitimacy to smooth re-entry. That possibility is examined by focusing on ex-combatants in South Africa and Northern Ireland who organised against the state, but later came to support conflict transformation in a radically altered state. Re-entry was thus a two-way process where ex-prisoners took up opportunities for inclusion while society worked to ensure their inclusion, thus allowing them to manage the problems of re-entry. The evidence is explored to show that this process was more successful in Northern Ireland than in South Africa.